(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Inscrutable Americans shows America as obsessed with sex. Right from bill boards to the lake party, sex plays a prominent role. Typical American youngsters, both urban and rural, are shown as changing their romantic or sexual partners every week. Libidinal pleasures of the physical body are to be satiated in an animalistic level in the Occident. But in the Oriental background, children are advised to abstain from romance, love and sex especially in the period of their education. Most of the Indian youths are advised not only to keep away from sex but even from non-vegetarian food which would instigate undesirable instincts. Being brought up strictly in a way which could be labelled as typically Indian, the psyche of Gopal the Indian youth, is subtle and designing and it needs the help of logic in matters of romance and sex, while Americans are shown as reckless and impulsive in the matters.